Thalictrum panzhihuaense (Ranunculaceae) is placed in synonymy with T. glandulosissimum, with reduction of T. tsaii to T. glandulosissimum var. tsaii - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum panzhihuaense (Ranunculaceae), described from Panzhihua city in southwestern Sichuan province, China, is conspecific with T. glandulosissimum and that T. tsaii, described from Weixi county in northwestern Yunnan province, China, is remarkably closely similar to T. glandulosissimum in all the other characters except the degree of glandulosity on plant body. We therefore place T. panzhihuaense in synonymy with T. glandulosissimum and treat T. tsaii as a variety of T. glandulosissimum, i.e. T. glandulosissimum var. tsaii. The identity of T. glandulosissimum var. chaotungense is also discussed. Lectotypification is proposed for T. glandulosissimum.